POLEMIK PELAKSANAAN MUTASI DAN OPEN BIDDING/SELEKSI TERBUKA DI KABUPATEN CIAMIS - Mochammad Iqbal Fadhlurrohman; Suswanta Suswanta; Etika Khairina (Jurnal Ilmu Pemerintahan Widya Praja, 2021)
In the reform era, efforts to improve the management system of Civil Servants (PNS) are necessary, such as building a clean government without making mistakes that are harmful to the state or region and society. One of the initiatives is to strengthen the bureaucratic structure that prioritizes the efficiency of civil servants with proper success intentions. In terms of efforts to improve the bureaucratic system, the mutation is one of them because the mutation attempts to improve one employee's poor performance or in the work that competent employees must carry out in their fields through mutation. This study uses a qualitative analysis method by describing the results of the mutations carried out by the Ciamis Regency government and data obtained from several attachments to the Regent's Decree and others related to this research. The results of data analysis carried out in this study are from the two mutations carried out by the Ciamis Regency government. This was by what should be done by looking at some of the regulations that apply in carrying out the mutation; the mutation was carried out two times, the first was mutation on October 21 2019 and the second, mutations were carried out using available selection or open bidding. Because there were so many Civil Servants who retired and there were also many PNS who mutated between Regencies, there were many vacancies in the high-ranking leadership positions. Keywords; Implementation Of Civil Servant Transfer, Civil Servant Transfer Problems, Open Selection